Thyroid Hormone Hyposensitivity: From Genotype to Phenotype and Back - Rurale, Giuditta; Cicco, Emery Di; Dentice, Monica; Salvatore, Domenico; Persani, Luca; Marelli, Federica; Luongo, Cristina (Frontiers in Endocrinology, 2020)
Thyroid Hormone Action Defects (THADs) have been classically considered conditions of impaired sensitivity to thyroid hormone (TH). They were originally referring to alterations in TH receptor genes (THRA and THRB), but the discovery of genetic mutations and polymorphisms causing alterations in cell membrane transport (e.g. MCT8) and metabolism (e.g. SECISBP2, DIO2) led recently to a new and broader definition of TH hyposensitivity (THH), including, not only THADs, but all defects that could interfere with the activity of TH. Due to the different functions and tissue-specific expression of these genes, affected patients exhibit highly variable phenotypes. Some of them are characterized by a tissue hypothyroidism or well-recognizable alterations in the thyroid function tests (TFTs), whereas others display a combination of hypo- and hyperthyroid manifestations with normal or only subtle biochemical defects. The huge effort of basic research has greatly aided the comprehension of the molecular mechanisms underlying THADs, dissecting the morphological and functional alterations on target tissues, and defining the related-changes in the biochemical profile. In this review, we describe different pictures in which a specific alteration in the TFTs (TSH, T4, and T3 levels) is caused by defects in a specific gene. Altogether these findings can help clinicians to early recognize and diagnose THH, and to perform a more precise genetic screening and therapeutic intervention. On the other hand, the identification of new genetic variants will allow the generation of cell-based and animal models to give novel insight into thyroid physiology and establish new therapeutic interventions.